2023
DOI: 10.1002/smll.202307241
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐Doped Bimetallic (Co,Ni)2P Integrated CoP in N,S Co−Doped Carbon: Unveiling a Compatible Hybrid Electrocatalyst for Overall Water Splitting

Mani Ram Kandel,
Uday Narayan Pan,
Purna Prasad Dhakal
et al.

Abstract: Rational design of highly efficient noble‐metal‐unbound electrodes for hydrogen and oxygen production at increased current density is crucial for robust water‐splitting. A facile hydrothermal and room‐temperature aging method is presented, followed by chemical vapor deposition (CVD), to create a self‐sacrificed hybrid heterostructure electrocatalyst. This hybrid material, (Mn−(Co,Ni)2P/CoP/(N,S)−C), comprises manganese‐doped cobalt nickel phosphide (Mn−(Co,Ni)2P) nanofeathers and cobalt phosphide (CoP) nanocub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that the addition of heterogeneous metals can alter the electronic structure of monometallic phosphides, thereby improving their catalytic efficiency [18][19][20]. On this basis, we constructed a bimetallic NiCoP heterojunction to modulate the intrinsic electronic distribution and enhance the H* coverage on the catalyst surface during HER under alkaline conditions, making NiCoP a promising candidate for efficient HER catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the addition of heterogeneous metals can alter the electronic structure of monometallic phosphides, thereby improving their catalytic efficiency [18][19][20]. On this basis, we constructed a bimetallic NiCoP heterojunction to modulate the intrinsic electronic distribution and enhance the H* coverage on the catalyst surface during HER under alkaline conditions, making NiCoP a promising candidate for efficient HER catalysis.…”
Section: Introductionmentioning
confidence: 99%